Global Meat Consumption Trends and Local Deforestation in Madre de Dios: Assessing Land Use Changes and other Environmental Impacts. (2015) - Recanati, F.; Allievi, F.; Scaccabarozzi, G.; Espinosa, T.; Dotelli, G.; Saini, M.
Abstract: Meat consumption is becoming one of the most relevant sectors in terms of environmental impacts globally. In the Brazilian Amazon the effects of this process are seen in the ongoing deforestation and land-use change (about 65% of deforestation can be linked to cattle ranching). One of the main causes of this trend is the increased efficiency of the transport infrastructure: along both sides of the Brazilian Inter-Oceanic highway, about 50 km of rainforest have been converted to cattle ranching. In 2011 the Inter-Oceanic highway was finalized also on the Peruvian side: the region of Madre de Dios is neighboring the Brazilian Amazon, therefore the risk is that this area will undergo the same kind of development. The objective of this analysis is to highlight the contribution of global meat demand trend as cause of land use change and deforestation in the Madre de Dios region. This focus has been chosen since, nowadays, the magnitude of cattle ranching activities is hidden by more evident and damaging activities (e.g., gold mining), and its near-future effects risk to be underestimated. By starting with investigating the preliminary signals of cattle ranching contribution to the local deforestation process, this analysis will serve as basis for more comprehensive future works on local data, including monitoring campaigns of local biodiversity and GHG emissions. Land-use change is, thus, analyzed through FAO data and also through data acquired with remote sensing carried out within other projects. Meat consumption and production outcomes are obtained from the FAOSTAT database. By integrating trends in the regional meat consumption with the emerging trading effects, which are incremented by the new highway, it is possible to highlight the risk that the global convergence in meat consumption trends can locally influence the deforestation in Madre de Dios.